First vocal album Vol. 342 songs with pianoforte accompaniment - Schubert, Franz (G. Schirmer. Inc., 1895)
WanderingnWhithernHalt by the BrooknThanks to the BrooknAfter worknThe questionnImpatiencenMorning greetingnThe Miller's